Ethics - Ariola, Mariano M. (Intramuros, Manila, Philippines : Unlimited Books Library Services and Publishing Inc., 2018)
This resource material has been prepared to comply with the mandate of CHED memorandum np. 20, S. 2013 requiring core subjects under the new general education curriculum to be outcome-oriented, interdisciplinary in scope and holistic in approach and broad enough to accomodate a wider range of perspectives and developemental approaches.
Part 1: An overview of the course -- Chapter 1 - Basic concepts in philosophy and ethics -- Chapter 2 - Moral dilemmas and the foundation of ethics -- Part II : Elements of moral experience -- Chapter 1 - The Moral agent -- Chapter 2 - The Moral art -- Part III : Taxation and globalization -- Chapter 1 - Taxation -- Chapter 2 - Moral challenges of globalization.
Includes bibliographical references.
Keywords: ETHICS -- STUDY AND TEACHING